Preparation and properties of modified asphalt using branch SBS/nanoclay nanocomposite as a modifier. Issue 6 (18th August 2019) - Martínez-Anzures, Jesús Daniel; Zapién-Castillo, Samuel; Salazar-Cruz, Beatriz Adriana; Rivera-Armenta, José Luis; Antonio-Cruz, Rocio del Carmen; Hernández-Zamora, Gabriel; Méndez-Hernández, María Leonor
Abstract : The use of Closite 15A and a triblock copolymer branch type (BP) as asphalt modifiers was studied. Modified asphalt binder was prepared by adding nanocomposites (NCs) of styrene–butadiene–styrene copolymer (BP) and Cloisite 15 A (NCMM). The NCs were obtained by means of a melt mixing technique. The morphology of the modified asphalt blends was observed via fluorescence microscopy, which revealed a good dispersion pattern of NCMM into the asphalt binder, and explains to a considerable extent, their final rheological behaviour. The modified asphalts exhibited a relatively high complex modulus compared to the unmodified asphalt and, as a consequence displayed enhanced viscoelastic properties. NCMM increased slightly both the softening point and the viscosity of the modified asphalts at elevated temperatures, and had a compatibilising effect on them, which was shown as an improvement of their storage stability.